MODEL OF DEGENERATE DWARF WITH SPIN-POLARIZED ELECTRON SYSTEM - Vavrukh, M. V.; Dzikovskyi, D. V.; Tyshko, N. L. (Одеські астрономічні публікації, 2016)
A three-parametric model of a massive degenerate dwarf was proposed. Unlike paramagnetic state of electron system in the standard Chandrasekhar model electrons are considered in a partially spin-polarized state. The parameters of the model are: x0 – the relativism parameter at stellar centre, μe = < Z/A > – the average chemical composition parameter and ζ – the degree of spin polarization of the electron system. The macroscopic characteristics (e.g. mass, radius, energy) as functions of the model parameters were obtained from the solution of the mechanical equilibrium equation. The electron spin polarization was shown to lead to the increase of stellar radius and especially to mass compared with the corresponding characteristics of the standard model. The application of the proposed model to interpreting the stability of massive dwarfs in binary system was discussed.